SOCIAL EXCLUSION IN INDONESIA MILITARY HOSPITAL - Haifa Pasca Nadira Suar (Indonesian Journal of Health Administration, 2023)
Background: In the era of the COVID-19 pandemic, one of the social protections in Indonesia that still requires special attention is the protection of public health. Aims: This study aims to analyze the principles of social protection in the Social Security Agency for Health (BPJS Kesehatan) and the implementation of inclusive health services in Indonesia Military Hospital. Methods: This study used a qualitative approach by conducting in-depth interviews and made direct observations for one month by observing the processes and phenomena that occurred at the dr. Esnawan Antariksa Air Force Hospital as a case study. Results: The root cause of social exclusion in health services in military institutions was an aspect of the inherent hierarchy that caused exclusion in the income dimension triggered by socioeconomic level, status, and background of patients so that patients did not get the same rights in obtaining health services. Conclusion: Implementing social protection through BPJS Kesehatan in military-based hospitals caused patients with specific groups to experience layered exclusion. Patients who wanted to receive healthcare at military hospitals had differences in the stages of receiving them. However, the quality of medical services doctors and other health workers provided were not discriminatory. Keywords: BPJS kesehatan, health services, military hospital, social exclusion, social protection